Patients' Response to Waiting Time in an Out-Patient Pharmacy at a Tertiary Care Hospital - Meena Kumari K, Somu, Mohan Amberkar, Nandit P.B (Journal of Applied Pharmaceutical Science)
This study was carried on to know the average time taken from when the customer arrives in out-patient pharmacy till the collection of medicine and to know the time spent at various counters in the out-patient pharmacy. It was an observational study done on customers attending hospital pharmacy for a period of two months. Seventy out-patients were randomly selected from the population of patients who attended pharmacy. Similarly dispensing operations were observed. Workflow analysis method and stop watch techniques were used to measure patient waiting time. The various places where the customer has to wait from billing till the procurement of medicine was noted and also the total time taken. A total of 35 patients / patient attender’s were observed both in the morning and in the evening. Majority of the time was consumed in billing after placing the prescription on the dispensing table .It was seen that in the morning session the waiting time for the various components of processing was less compared to the afternoon, except for the processing of the transaction time by the cashier is more in the morning (38.34±34.66) sec compared to (28.42±25.67) sec. Majority of the time was consumed in billing after placing the prescription on the dispensing table.
Keywords: Out-patient Pharmacy,waiting time,patient queue.